Explore the Protective Role of Obesity in the Progression of Myocardial Infarction - Zhao, Siyuan; Cao, Rongyuan; Zhang, Shuhua; Kang, Yan (Frontiers in Cardiovascular Medicine, 2021)
Obesity has been shown as a risk factor to increase the incidence of myocardial infarction (MI) but also been suggested to play a protective role in decreasing the modality of accurate MI with unknown mechanisms. Here, we firstly used large-scale literature data mining to identify obesity downstream targets and MI upstream regulators with polarity, based on which the Obesity-MI regulatory networks were constructed. Then, a gene set enrichment analysis was conducted to reveal the functional profile of the genes involved in the obesity-MI regulatory networks. After that, a mega-analysis using MI RNA expression datasets was conducted to test the expression of obesity-specific genes in the case of MI, followed by a shortest-path analysis to explore any potential gene-MI association. Literature-based networks analysis showed that obesity inhibits 11 MI promoters that were mainly involved in blood pressure related networks, including NPPB, NPPA, IRS1, SMAD3, MIR155, ADRB1, AVP, MAPK14, MC3R, ROCK1, and COL3A1. Mega-analysis revealed another potential MI→PTH→MI networks that need further validation. Our results suggested that obesity may play a protective role in the progression of MI by lifting the blood pressure, which may add new insights into the understanding of the obesity-MI relationship.